Influence of Chute Slope on Oxygen Content in Stepped Waterways - Baylar, Ahmet; Emiroglu, M. Emin; Bagatur, Tamer (Gazi Univ, 2009)
Water quality and its enhancement have a close connection with the presence of dissolved oxygen. In fact, the oxygen concentration in surface waters is a prime indicator of the water quality for human use as well as for the aquatic biota. The physical process of oxygen transfer or oxygen absorption from the atmosphere acts to replenish the used oxygen. This process is termed re-aeration or aeration. Aeration enhancement by macro-roughness is well-known in water treatment, and one form is the aeration cascade. The macro-roughness of the steps significantly reduces flow velocities and leads to flow aeration along the stepped cascade. This paper seeks influence of channel slope on oxygen content in stepped cascade aerators. It is demonstrated that the aeration efficiency of the stepped cascade aerators increases with increasing channel slope.
Keywords: Aeration efficiency; Oxygen transfer; Stepped waterway; Chute slope